Studies of sulfonated poly(phenylene)-block-poly(ethersulfone) for proton exchange membrane fuel cell. (27th April 2017) - Jang, Hohyoun; Ryu, Taewook; Sutradhar, Sabuj Chandra; Ahmed, Faiz; Choi, Kunyoung; Yang, Hanmo; Yoon, Sujin; Kim, Whangi
Abstract: The polymers were prepared by nickel catalyzed carbon–carbon coupling reaction of 1, 4-dichloro-2, 5-dibenzoylbenzene (DCDBB) and sulfone oligomer. DCDBB was synthesized from oxidation reaction of 2, 5-dichloro-p-xylene and followed by Friedel–Craft reaction with benzene. DCDBB monomer had good reactivity in polymerization by electron withdrawing group as benzophenone. Sulfone group of oligomer had improving flexibility and solubility. Post sulfonation was carried out to add sulfonic acid groups by using chlorosulfuric acid. These polymers were presumably stable against nucleophilic attack by hydrogen peroxide, hydroxide anion, and radical generated by proton exchange membrane fuel cell operation system. The number of sulfonic acid groups were controlled by varying the mole ratio of 1, 4-dichloro-2, 5-dibenzoylbenzene in synthesized polymer. A series of membranes were studied by 1 H NMR spectroscopy, thermo-gravimetric analysis, ion exchange capacity, water uptake, and proton conductivity. Also surface morphologies were assessed by atomic force microscope (AFM). Highlights: The sulfonated polyphenylenes containing sulfone moiety were synthesized. The degree of sulfonation was controlled by reaction time. Complex catalyst was more reactivity than unitary catalyst at sulfone monomer. Membranes have good morphology, flexibility and chemical stability.